2017
DOI: 10.1073/pnas.1608106114
|View full text |Cite
|
Sign up to set email alerts
|

A network perspective reveals decreasing material diversity in studies on nanoparticle interactions with dissolved organic matter

Abstract: Dissolved organic matter (DOM) strongly influences the properties and fate of engineered nanoparticles (ENPs) in aquatic environments. There is an extensive body of experiments on interactions between DOM and ENPs and also larger particles. [We denote particles on the nano-and micrometer scale as particulate matter (PM).] However, the experimental results are very heterogeneous, and a general mechanistic understanding of DOM-PM interactions is still missing. In this situation, recent reviews have called to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Colloidal stability of NP is one of the key factors controlling their fate and effects [ 12 , 89 ]. When released into the environment, NP interact with the variety of dissolved or particulate, inorganic or organic compounds influencing NP aggregation dynamics and thus colloidal stability [ 90 ]. Ultimately, exposure conditions are controlled by NP aggregation.…”
Section: Fate Of Nanoparticles In the Environmentmentioning
confidence: 99%
“…Colloidal stability of NP is one of the key factors controlling their fate and effects [ 12 , 89 ]. When released into the environment, NP interact with the variety of dissolved or particulate, inorganic or organic compounds influencing NP aggregation dynamics and thus colloidal stability [ 90 ]. Ultimately, exposure conditions are controlled by NP aggregation.…”
Section: Fate Of Nanoparticles In the Environmentmentioning
confidence: 99%
“…For this reason, recent reviews have called to diversify the types of DOM and PM studied in the experiments [ 10 , 12 ]. However, in our previous work we found that there is an overall decrease, rather than an increase, in the diversity of studied DOM-PM combinations [ 11 ]. PM types studied most often are titanium dioxide and silver nanoparticles; rarely studied are, e.g., quantum dots (note that PM and ENPs are not distinct categories, but PM includes ENPs).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain insights applicable to a broad range of DOM and ENP types, both from correlations and from mechanistic studies, there is a need to study the interactions between DOM and particulate matter (PM), i.e., ENPs and particles of larger size, for a range of chemically and structurally diverse DOM and ENP types [ 11 ]. For this reason, recent reviews have called to diversify the types of DOM and PM studied in the experiments [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations